2022
DOI: 10.3233/shti220597
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Undergraduate Medical Education

Abstract: AI will take on an increasingly important role in medicine. Therefore, AI competencies should be taught in medical school. We investigated the inventory of AI-related courses at German medical schools. The majority of faculty offer courses on AI, but mainly at the elective and introductory levels. Regarding the topic of AI, there is a gap in German medical education that should be closed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In terms of quantitative studies, the level of evidence was categorized as follows: 5 studies utilized face validity, 3,5,7,8,18 3 studies content validity, 4,24,26 and seventeen studies used both face and content validity. [5][6][7][8][9][11][12][13][14]16,18,20,22,[25][26][27][28] In articles related to the development and validation of AI tools, it was observed that Support Vector Machines (SVMs) were used in half of the studies (5 out of 10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of quantitative studies, the level of evidence was categorized as follows: 5 studies utilized face validity, 3,5,7,8,18 3 studies content validity, 4,24,26 and seventeen studies used both face and content validity. [5][6][7][8][9][11][12][13][14]16,18,20,22,[25][26][27][28] In articles related to the development and validation of AI tools, it was observed that Support Vector Machines (SVMs) were used in half of the studies (5 out of 10).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of quantitative studies, the level of evidence was categorized as follows: 5 studies utilized face validity, 3,5,7,8,18 3 studies content validity, 4,24,26 and seventeen studies used both face and content validity. [5][6][7][8][9][11][12][13][14]16,18,20,22,[25][26][27][28] In articles related to the development and validation of AI tools, it was observed that Support Vector Machines (SVMs) were used in half of the studies (5 out of 10). 30,32,33,36,38 Neural networks (NN) were utilized in 3 out of 10 studies, [33][34][35] Naive Bayes 3 out of 10 studies, [32][33] and K-nearest neighbour in 2 out of 10 studies, [37][38] forming the other commonly used AI tools (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As technology rapidly advances, AI will increasingly play a crucial role in the future of health care [ 12 13 ]. This also requires restructuring medical curricula to adapt to dynamic technological advances to prepare students for the changing structures of medical practice [ 14 15 ].…”
Section: Introductionmentioning
confidence: 99%